Efficacy of sucrose verses expressed breast milk for pain among neonates receiving vaccination, in india - MRS. SUJATHA.S,; DR. REBECCA SAMSON,; DR. BRIDGITTE AKILA,; DR. SUNDARESAN, (International Journal of Pharma and Bio Sciences, 2017)
A study with the objective to assess the efficacy of Expressed Breast Milk and 24% oral sucrose in combination with Facilitated tucking during intradermal Injection in term neonates. Healthy term neonates who fulfilled the inclusion criteria were included in the study using simple random technique. The study intervention consists of administration of 1 ml of 24% oral sucrose or 2ml of Expressed Breast Milk, 2 minutes before Bacillus Calmette Guerin Vaccination through intradermal route and facilitated tucking at the time of vaccination. The primary outcome measure of cumulative Neonatal and Infant Pain Scale score at 0, 3, 5 minutes and the respiratory rate, heart rate before and after intradermal injection for neonates of study groups was significantly lower than for neonates of control group. Oral administration of 24% sucrose solution given 2 minutes before injection was effective than Expressed Breast Milk in reducing acute neonatal pain following BCG Vaccination.